Construing Indonesia's maritime diplomatic strategies against Vietnam's illegal, unreported, and unregulated fishing in the North Natuna Sea. Issue 4 (2nd October 2022) - Darwis,; Putra, Bama Andika
Abstract: The bilateral relations between Indonesia and Vietnam have long been problematic due to the unresolved maritime borders surrounding the North Natuna Sea. Despite having a long history of cooperation in multilateral forums such as ASEAN (Association of Southeast Asian Nations), the increasing occurrence of IUUF (illegal, unreported, and unregulated fishing) in the North Natuna Sea continues to raise concerns in Jakarta about vessels of different countries, including Vietnamese-flagged vessels. Taking an example, this study evaluates the maritime diplomatic strategies of the President Joko Widodo (Jokowi) administration against the encroachment of Vietnam fishing boats which entered Indonesian waters in the North Natuna Sea between 2020-2021 with reference to the response of 1) Indonesia's navy; (2) the Indonesian Maritime Security Agency, and (3) Indonesian Police or Ministry of Marine Affairs and Fisheries. Although there have been hundreds of incidents, five analytical cases were evaluated in this paper based upon their maritime diplomatic properties to understand Indonesia's contemporary strategy toward such encroachments. Using Le Mière's five framework points, the study argues that Indonesia's maritime diplomatic strategies against Vietnam's IUUF exhibited 1) a kinetic effect; 2) consistency; 3) message explicitness; 4) reactive diplomacy; and 5) lack of power balance among stakeholders.